Occupational challenges of physicians involved in tuberculosis control in China: a qualitative study. (October 2016) - Chen, Shanquan; Zhang, Hui; Qu, Yan; Wu, Yushan; Long, Qian; Ran, Limei; Xue, Qiuji; Chen, Kai; Luo, Fei; Yao, Lan; WONG, Lai-yi; FUNG, Hong; et al.
Abstract: Background: Despite its dramatic improvement, China's tuberculosis burden is still high according to the 2015 WHO TB report. Evidence show that experienced physicians do better in reducing delay diagnosis and patient mortality and are more likely to follow the treatment guidelines. However, in China, few studies have focused on physicians specialised in tuberculosis; and these few studies were mainly centred on the prevalence and risk factors among them. We assessed the occupational challenges of these physicians in China. Methods: We conducted 14 focus group discussions in Yichang City of the Hubei Province and in Hanzhong City of the Shaanxi Province, China between May 5, 2013, and Aug 11, 2015. We purposively sampled 169 physicians, 92 from Yichang, to ensure representation and geographical diversity. Health administrators, doctors and nurses, who are currently responsible for the tuberculosis care, were included. Interviewers used open-ended discussion guides concerning occupational risk, workload, work-reward, and challenges encountered. Data were transcribed verbatim and were coded, sorted, and classified by the thematic framework using Nvivo 11.0. Ethical permission was obtained from the Institutional Ethics Committee of Chinese Center for Disease Control and Prevention (CDC). Findings: 169 (100%) physicians specialised in tuberculosis considered that they are working in high-risk departments bearing heavy workloads with insufficient compensation. The amount of workload given to the physicians seems to have increased. The integrated approach shifted the clinical tuberculosis care from the CDCs to general hospitals, resulting in hospitals having to do excessive things including detection, diagnosis, and treatment and case management. To facilitate patients' compliance, all of the physicians have also been responsible for the hand out of subsidy and reimbursement. Due to inflexible information system, physicians have to handle patients' information by handwriting all the details on paper. The disunity between the three basic insurances seems to add to this additional workload. 160 (95%) seemed to be discontent with their compensation; they did not feel their reward reflects their increased workload, or sometimes it is even lower than what it was before, resulting in abhorrent attitude. 101 (60%) physicians still worried about occupational exposure and external prejudice, which reflects the high-risk work. Interpretation: To our knowledge, this is the first study focusing on tuberculosis physicians and their benefits. These findings should help policy makers and perfect the tuberculosis control. Funding: Natural Science Foundation of China (71203068 and 71573095) and the China National Health and Family Planning Commission and the Gates Foundation TB Project (51914). The funders had no role in the study.